Kelengkapan dan Ketepatan Pemberian Imunisasi Dasar Pentabio Dengan Kejadian Infeksi Saluran Pernafasan Akut (ISPA) Pada Batita: Indonesian - Anggraeni, Enissa Alvionita; Mansur, Herawati; Sondakh, Jenny JS (Malang Journal of Midwifery (MAJORY), 2021)
The decline in immunization coverage in Indonesia is followed by high mortality and morbidity for toddlers, one of which is caused by Acute Respiratory Infections. The government conducted an immunization program aimed at primary prevention of diseases that cause ARI with pentabio immunization. This research aims to determine the correlation between the completeness and accuracy of pentabio basic immunization with the incidence of acute respiratory infections (ARI) in toddlers in Dinoyo Public Health Center in Malang. The design of this research was correlation analytic using documentation studies on medical records, immunization registers and infant cohorts through a retrospective approach. The sample used was all sick toddlers who checked themselves in Dinoyo Community Health Center Malang City in July-September 2019 who met the inclusion criteria of 164 respondents using total sampling technique. The results of the analysis using the Chi Square Test obtained p-value of 0,000 (? ? 0.05) followed by a Contingency Coefficient Test with a value of C = 0.426 indicating that there was a significant relationship between the completeness and accuracy of pentabio basic immunization with the incidence of acute respiratory infections at toddler at Dinoyo Public Health Center in Malang City with a moderate level of closeness. Pentabio basic immunization given precisely and completely can prevent ARI in toddlers. Health facilities and midwives are expected to increase public awareness about the importance of completeness and accuracy in providing basic immunization for pentabio according to the basic immunization delivery schedule. Keywords: Completeness And Accuration, Pentabio Basic Immunization, ARI, Toddlers